Venus - Brewer, Duncan, 1938- (New York : Marshall Cavendish, 1993)
Examines the physical characteristics and conditions of Venus, describing its position in relation to the sun and other planets and surveying humanity's attempts to penetrate its mysteries.
Includes bibliographical references (p. 61) and index.
Keywords: Venus (Planet) -- Juvenile literature; Venus (Planet)